Injury Incidence Across the Menstrual Cycle in International Footballers - Martin, Dan; Timmins, Kate; Cowie, Charlotte; Alty, Jon; Mehta, Ritan; Tang, Alicia; Varley, Ian (Frontiers in Sports and Active Living, 2021)
Objectives: This study aimed to assess how menstrual cycle phase and extended menstrual cycle length influence the incidence of injuries in international footballers. Methods: Over a 4-year period, injuries from England international footballers at training camps or matches were recorded, alongside self-reported information on menstrual cycle characteristics at the point of injury. Injuries in eumenorrheic players were categorized into early follicular, late follicular, or luteal phase. Frequencies were also compared between injuries recorded during the typical cycle and those that occurred after the cycle would be expected to have finished. Injury incidence rates (per 1,000 person days) and injury incidence rate ratios were calculated for each phase for all injuries and injuries stratified by type. Results: One hundred fifty-six injuries from 113 players were eligible for analysis. Injury incidence rates per 1,000 person-days were 31.9 in the follicular, 46.8 in the late follicular, and 35.4 in the luteal phase, resulting in injury incidence rate ratios of 1.47 (Late follicular:Follicular), 1.11 (Luteal:Follicular), and 0.76 (Luteal:Late follicular). Injury incident rate ratios showed that muscle and tendon injury rates were 88% greater in the late follicular phase compared to the follicular phase, with muscle rupture/tear/strain/cramps and tendon injuries/ruptures occurring over twice as often during the late follicular phase compared to other phases 20% of injuries were reported as occurring when athletes were “overdue” menses. Conclusion: Muscle and tendon injuries occurred almost twice as often in the late follicular phase compared to the early follicular or luteal phase. Injury risk may be elevated in typically eumenorrheic women in the days after their next menstruation was expected to start.